Molecular Diagnostic Tools for Nematodes - Christoforou, Michalakis; Oxford, Michael; Tsaltas, Dimitrios (My University, 2017)
The phylum of Nematoda is a species‐rich taxonomic group in abundant numbers across a wide range of habitats, including plant and animal pathogens, as well as good environmental health indicators. Morphological observations are of low throughput and more importantly have problems with their discriminatory capacity, particularly at the species level. For these reasons, diagnostic tools are of paramount importance for all fields of human, animal and plant nematology as well as for environmental studies in water and soil. Accurate, fast and low‐cost methodologies are required in order to identify and quantify the population of nematodes in samples from various sources. Scientists in basic research as well as in routine application fields need to have tools for resolving these identification obstacles. Their decisions can be human‐, animal‐ or plant‐health related, while many times legally committing. As a result, applicable and accredited methods are required and should be readily available in a common routine lab or in the field of battle or at border control agencies. This chapter aims to inform with the most current information on the available tools for nematode diagnostics, their positives and negatives and hints about the trends in the field and suggestions for those who would like to pursue further this field of biotechnology as researchers or simple users.
Keywords: molecular; Nematodes; Identificaation